2004
DOI: 10.1111/j.1524-4725.2004.30256.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neck Lines and Forehead Rhytids with a Nonablative 1540-nm Er:Glass Laser: A Controlled Clinical Study Combined with the Measurement of the Thickness and the Mechanical Properties of the Skin

Abstract: This study demonstrates that irradiation with a 1540-nm Er:Glass laser emitting in a pulsed mode and coupled with an efficient contact cooling system increases dermal thickness and firmness, leading to a clinical improvement of neck lines and forehead rhydits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 50 publications
0
41
0
1
Order By: Relevance
“…Some of the most common include suction tests (Alexander and Cook 1977;Elsner et al 1990;Diridollou et al 1998;Hendriks et al 2003), torsion tests (Escoffier et al 1989), indentation tests (Highley 1977), uniaxial tests (Snyder and Lee 1975), biaxial tests (Lanir and Fung 1974a;Schneider et al 1984) and multiaxial tests (Reihsner et al 1995). Recent work has tended to focus toward applying suction devices in combination with either an ultrasound (Diridollou et al 2000(Diridollou et al , 2001Hendriks et al 2003;Dahan et al 2004) or an OCT imaging device (Hendriks et al 2004) to measure the stress distribution in deformed skin. These devices are, however, inadequate for modelling purposes as they do not account for the anisotropic nature of skin.…”
Section: Introductionmentioning
confidence: 97%
“…Some of the most common include suction tests (Alexander and Cook 1977;Elsner et al 1990;Diridollou et al 1998;Hendriks et al 2003), torsion tests (Escoffier et al 1989), indentation tests (Highley 1977), uniaxial tests (Snyder and Lee 1975), biaxial tests (Lanir and Fung 1974a;Schneider et al 1984) and multiaxial tests (Reihsner et al 1995). Recent work has tended to focus toward applying suction devices in combination with either an ultrasound (Diridollou et al 2000(Diridollou et al , 2001Hendriks et al 2003;Dahan et al 2004) or an OCT imaging device (Hendriks et al 2004) to measure the stress distribution in deformed skin. These devices are, however, inadequate for modelling purposes as they do not account for the anisotropic nature of skin.…”
Section: Introductionmentioning
confidence: 97%
“…In the long-term follow-up (from 6 months to 2 years) the average reduction of the acne was between 72 and 75%. A number of studies [75,76] have indicated not only a considerable improvement in skin defects but also a general recovery of the surrounding tissues after non-ablative FP.…”
Section: Reviewsmentioning
confidence: 99%
“…Studies [75] showed the effect of non-ablative fractional laser treatment of wrinkles on the neck and forehead by 3 months after treatment. Their smoothing, as well a significant increase in thickness and resilience of the skin in general, was registered.…”
Section: Reviewsmentioning
confidence: 99%
“…For example, the temperature-time relation resulting in the induction of heat shock protein could produce or enhance the wound healing process around the ablated and/or coagulated zone [54]. In the laser bulk heating and dermal coagulation of the dermis, superficial cryogenic or contact cooling is used to protect the epidermis; this treatment modality purportedly stimulates collagen remodeling [49].…”
Section: Trends and Future Direction Of Lasers In Dermatologymentioning
confidence: 99%
“…This is often done with the CO2 and pulsestacked Er:YAG lasers. In laser bulk heating and dermal coagulation of the dermis, superficial cryogenic or contact cooling is used to protect the epidermis; this treatment modality purportedly stimulates collagen remodeling [49]. The former removes superficial pigmentary lesions and flattens fine lines and rhytids, while the latter ' ' reduces rhytids and furrows by an increased volume of the underlying dermal collagen.…”
Section: Trends and Future Direction Of Lasers In Dermatologymentioning
confidence: 99%